Technology Innovations and Process Improvements for “The Last Mile Delivery” Supply Chain - Mishra, Praveen Kumar (Digital Repository of Theses - SSBM Geneva, 2024)
E-commerce retail sales have been growing year on year (YOY), marking a cultural mindset change in purchaser and making them sway to online purchases as compared to traditional window shopping. This mindset took a great faith of leap, with Covid-19, directly impacting lives and businesses across the globe. Change in mindset gave way to unique demands, like expecting delivery in same day or in next 45 minutes as a new normal expectation. These demands led researchers, supply chain domain experts, logistics & delivery partners as well as e-commerce vendors to ponder over ways by which business processes could be made more agile – simpler – faster with additional advantages of shelving out business process inefficiencies as well as reducing the cost of operations by bringing business very near to consumer. This research was an attempt to study how co-ownership/ co-sharing of infra resources and technology embracing can help e-commerce vendors become more agile and can meet the expectations of end consumers for a delivery model to optimize from 1 week to 1 day to 45 minutes. The research used Mixed Method research approach where-by quantitative and qualitative data was collected from different targeted audiences. Theoretical framework of e-business competitiveness was used to derive a web-based online survey targeted to e-consumers, e-commerce vendors, logistics and delivery partners including detailed interviews of selected respondents. The findings of the research indicate that consumers at large are now inclined to have daily need products from online shopping, and they are willing to pay extra if the delivery time is quick and is adhering to quality standards. At the same time, the e-commerce vendors and logistics partners are willing to adopt or fund technology adoption and innovation for supporting quick delivery to customers. It has also been discovered from the data that there are small players in the business too who cannot afford to keep pace with technology changes, but they are willing to piggy ride some big players and contribute to the success of quick e-commerce. This research study will be helpful for e-commerce vendors as well as partners in e-commerce delivery value chain.